Uterus Transplantation and Pregnancy Induction: An Approved Protocol at Royal Prince Alfred Hospital (RPA) - Dana GEORGEVSKY; Ying LI; Selvan PATHER; Trevor TEJADAS-BERGES; David ROBINSON; Jerome LAURENCE; Neil CAMPBELL; Kate WYBURN; Keith LIYANAGAMA; Rajit NARAYAN; Tracey LUTZ; Agnes CHAN; et al. (Fertility & Reproduction, 2022)
Background: Absolute Uterine Factor infertility (AUFI) can be congenital such as Mayer-Rokitansky Küster syndrome (MRKH), or acquired resulting from conditions rendering the uterus non-functional or hysterectomy. Prior to the year 2014, women with AUFI had limited opportunities to have a child with the options being either surrogacy or adoption. In 2014 the first successful uterus transplant (UT) was achieved in Sweden. RPA was the first site in Australia to receive ethical approval for a UT trial. Objectives: To determine if UT is an effective, safe, and operationally viable option for women with AUFI in order to achieve live birth. Methodology: Potential donor/recipient pairs will undertake a comprehensive screening process to assess suitability. The process will then involve: 1.Creation of embryos via IVF; 2.Donor Hysterectomy and Recipient Transplant; 3.Recovery with immunosuppression; 4.Embryo transfer; 5.Pregnancy care and delivery; 6.Post-delivery, potential second pregnancy, and explant with follow-up. Conclusion: UT is a novel and promising procedure for women with AUFI to achieve parenthood. The process involves a comprehensive workup to assess suitability. A multidisciplinary team within a tertiary centre is essential for establishing a successful UT program. Due to the infancy of UT all centres need to be diligent in reporting clinical outcomes to establish the feasibility of UT as a future treatment option for AUFI.